Вплив елементів мінерального живлення на ріст рослин різних екоморфотипів родини Araceae Juss. - Ivanytska, B.O.; Zaimenko, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of a set of experiments on an effect of mineral nutrition's elements on growth of plants with different ecomorphotypes of Araceae Juss. family are given in this article. Positive effect of superphosphate, potassium sulfate and aquarine on plant growth of tested species at the early stages of growth is determined. Unequal reaction of plants with different vital forms to mineral fertilizers application is proved. This fact must be considered for developing a technology of these species cultivation under the conditions of greenhouses.